2001
DOI: 10.1161/01.atv.21.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for Advanced Glycation End Products Mediates Inflammation and Enhanced Expression of Tissue Factor in Vasculature of Diabetic Apolipoprotein E–Null Mice

Abstract: Abstract-Advanced glycation end products (AGEs) and their cell surface receptor, RAGE, have been implicated in the pathogenesis of diabetic complications. Here, we studied the role of RAGE and expression of its proinflammatory ligands, EN-RAGEs (S100/calgranulins), in inflammatory events mediating cellular activation in diabetic tissue. Apolipoprotein E-null mice were rendered diabetic with streptozotocin at 6 weeks of age. Compared with nondiabetic aortas and kidneys, diabetic aortas and kidneys displayed inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
158
1
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 278 publications
(179 citation statements)
references
References 41 publications
12
158
1
8
Order By: Relevance
“…Diabetic mice demonstrated an upregulation of AGER, as has been shown previously [41]. We have demonstrated a novel finding, that gemfibrozil treatment was associated with an attenuation of Ager expression in diabetic mice.…”
Section: Discussionsupporting
confidence: 85%
“…Diabetic mice demonstrated an upregulation of AGER, as has been shown previously [41]. We have demonstrated a novel finding, that gemfibrozil treatment was associated with an attenuation of Ager expression in diabetic mice.…”
Section: Discussionsupporting
confidence: 85%
“…This chemokine has been reported to play an important role in the development of atherosclerosis in the apoE-null mouse in the absence 24 or presence of diabetes. 25 The endothelial adhesion molecule VCAM-1, which is important for the adhesion of macrophages to the vascular wall, 26,27 was also significantly increased in diabetes and was attenuated by irbesartan. Amlodipine did not have an effect on macrophage or vascular smooth muscle cell infiltration and proliferation or on VCAM-1 and MCP-1 expression, consistent with the failure of this agent to reduce atherosclerosis in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of RAGE by administration of genetically engineered sRAGE successfully prevented the development of micro- 132,133 and macrovascular complications in diabetes [134][135][136] . We have also shown that adenoviral overexpression of esRAGE successfully restored the impaired angiogenic response in diabetic mice 101 .…”
Section: F Circulating Srage and Esrage In Ckdmentioning
confidence: 99%